Penanaman Karakter Toleransi Melalui Pembelajaran Aqidah Akhlak di MI Al Muslimiyah Randublatung - Imam Ghozali; Moh Sholihuddin; Muh Misbahul Munir (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to describe the implementation of tolerance character education through Aqidah Akhlak learning at MI Al Muslimiyah Randublatung. This research employed a descriptive qualitative approach with the subjects consisting of the Aqidah Akhlak teacher and fifth-grade students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Aqidah Akhlak learning plays a crucial role in developing students' tolerance character through three main strategies: teacher role modeling, moral discussion activities, and religious social practices. Teacher role modeling emerged as the most dominant factor, as it provides direct examples of patience, fairness, and respect for diversity, while discussion and social activities foster empathy, cooperation, and social solidarity among students. The values of tolerance developed include respect for differences, justice, empathy, and anti-discrimination, aligning with the principles of Religious Moderation and the Profil Pelajar Pancasila (Pancasila Student Profile). This study concludes that the success of tolerance character formation depends not only on teaching methods but also on the consistency of teacher role modeling, contextual learning design, and a school culture that promotes humanity and togetherness.